The Influence Of Brand And Price On Consumer Purchase Intention Of Sunco Cooking Oil Products At Fresh Supermarket Ayahanda Medan - Dewi Nurmasari Pane (International Journal of Economics Accounting and Management, 2024)
Cooking oil is one of the basic necessities for the Indonesian people. The problem faced by the cooking oil company is a significant decline in sales among several other cooking oil products. This research aims to determine the influence of Brand and Price on the Purchase Intention of Sunco Cooking Oil Products at Fresh Supermarket Ayahanda Medan. Data collection by distributing questionnaires/surveys to 82 respondents. The model used with Multiple Regression and processed through SPSS. The results of this study show that Brand partially has a significant effect and Price partially has a significant effect on Purchase Intention. The R Square value is 0.601 or 60.1%, which means Brand and Price account for 60.1%, and the rest is explained by other factors.